The change of bile salt stimulated lipase during 6 months and the correlation with macronutrients in Chinese human milk - Ratna Nurmalita Sari; Lu Jing; Lv Jiaping (Hasanuddin University Food Science and Technology Study Program, 2023)
Bile salt stimulated lipase (BSSL) is the most abundant lipase in human milk which plays a pivotal role in new-born fat digestion, especially in the first six months of life. Lipid as the main energy supply for infant was very depending on BSSL activity for obtaining optimal lipid absorption under immature digestion track and pancreatic system condition. Due to the important role of BSSL, this research was addressed to study the effect of gender and lactation stage on BSSL activity and the correlation of BSSL with macronutrients content in Chinese human milk. Cross sectional and longitudinal study were used to investigate the BSSL activity and concentration pattern during 6 months of lactation. A declining pattern of both BSSL activity and concentration was observed as lactation stage progressed. The BSSL concentration significantly declined from 138.56 to 97.07 μg/ml during 6 months. Significant differences of BSSL activity and concentration were also observed in human milk for different gender babies. Male babies had breastmilk with less BSSL rather than female babies. Protein had strong correlation with BSSL activity and concentration, while carbohydrate had non-significant negative coefficient correlation. However, no correlation observed between fat content and BSSL.